Impact of climate change using CRAFT: a case study for West Africa - Shelia, Vakhtang; Faye, Babacar; Weber, Heidi; Hoogenboom, Gerrit (2020)
The CGIAR research program on Climate Change, Agriculture and Food Security Program’s (CCAFS) Regional Agricultural Forecasting Toolbox (CRAFT) is a framework for multi-scale spatial gridded simulations using an ensemble of crop models. The toolbox facilitates studies on the potential impact of climate change on crop production for a region in addition to other capabilities such as the regional in-season yield forecasting and risk assessment. CRAFT can be used to generate and conduct multiple simulation scenarios, maps, and interactive visualizations using a crop engine that can run the crop simulation models DSSAT, APSIM, and SARRA-H, in concert with the Climate Predictability Tool (CPT) for probabilistic seasonal climate forecasts.